2000
DOI: 10.1139/z00-140
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of capturing Kemp's ridley sea turtles, Lepidochelys kempii, in entanglement nets

Abstract: Blood samples were collected from 58 wild Kemp's ridley sea turtles (Lepidochelys kempii) to examine the physiological effects of capture in entanglement nets. Captured turtles were placed in holding tanks or in-water cages to examine whether the postcapture holding protocol influenced the time course of recovery of blood homeostasis. Lactate concentrations at capture were 4.5 ± 0.3 and 3.5 ± 0.3 mmol/L (mean ± SE) for L. kempii assigned to the in-water-cage and holding-tank treatments, respectively. Turtles h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 14 publications
2
20
1
Order By: Relevance
“…We found that longer entanglement times resulted in pronounced disruptions in blood biochemistry and were associated with lower physical grades (Tables 1 and 2). In general, blood parameters that did not vary significantly with increased gillnet entanglement time fell within the range of published values for healthy, wild-caught green sea turtles (Bolten and Bjorndal 1992, Aguirre et al 1995, Hasbún et al 1998, whereas parameters that were significantly impacted by gillnet entanglement time were in agreement with literature values for sea turtles exposed to stressors (Lutz and Dunbar-Cooper 1987, Gregory et al 1996, Hoopes et al 2000, Jessop et al 2002, Harms et al 2003.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…We found that longer entanglement times resulted in pronounced disruptions in blood biochemistry and were associated with lower physical grades (Tables 1 and 2). In general, blood parameters that did not vary significantly with increased gillnet entanglement time fell within the range of published values for healthy, wild-caught green sea turtles (Bolten and Bjorndal 1992, Aguirre et al 1995, Hasbún et al 1998, whereas parameters that were significantly impacted by gillnet entanglement time were in agreement with literature values for sea turtles exposed to stressors (Lutz and Dunbar-Cooper 1987, Gregory et al 1996, Hoopes et al 2000, Jessop et al 2002, Harms et al 2003.…”
Section: Discussionsupporting
confidence: 87%
“…Entanglement times of as little as 30 minutes resulted in elevated plasma lactate. The highest lactate value recorded in our study (50.6 mmol/L) was 2-8 times higher than maximum values for blood lactate reported in other studies of sea turtle entanglement in fishing gear (6.2-20 mmol/L; Lutz and Dunbar-Cooper 1987, Hoopes et al 2000, Harms et al 2003. The average blood lactate concentration for green turtles in our study (30.6 6 10.2, n 5 12) was 9 times higher than average blood lactate concentration of rehabilitated captive green turtles not exposed to a stress protocol and just prior to release (3.4 6 1.1, n 5 10; C. Harms, NC State University Center for Marine Sciences and Technology, and J. Beasley, Karen Beasley Sea Turtle Rescue and Rehabilitation Center, unpublished data).…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…In response to a decrease in blood pH, cells may release K + into the bloodstream in exchange for H + ions. A K + -H + exchanger has been proposed as a buffering mechanism to counteract blood acidosis in sea turtles (Rose 1977, Lutz 1997, Stabenau & Vietti 2003, Hoopes et al 2000, but the membrane proteins that may serve this function have not yet been identified in the cells of sea turtles. Increased plasma Cl -may reflect increased activity of the chloride shift mechanism of red blood cells in response to respiratory acidosis.…”
Section: Discussionmentioning
confidence: 99%